Pengaruh Motivasi Dan Disiplin Kerja Terhadap Kinerja Karyawan PT. Duta Mitra Lestari Jakarta Timur - Nafa Firliadhila; Rosento Rosento (Universitas Kristen Indonesia Toraja, 2024)
This study aims to analyze the influence of motivation and work discipline on employee performance at PT. Duta Mitra Lestari. The research method used was quantitative with a saturated sample, collecting data through questionnaires distributed to 60 employees of the company. The results indicate that the work motivation variable significantly influences employee performance, supported by a significance value of 0.021 < 0.05 and a T value of 2.369, which is greater than the critical T value of 2.002. The work discipline variable also shows a significant influence on employee performance with a significance value of 0.000 < 0.05 and a T value of 4.382. Simultaneous analysis indicates that motivation and work discipline together significantly affect employee performance, with an F value of 82.992 and an R Square of 0.744, indicating that 74.4% of the variability in employee performance is influenced by these variables. This study implies that the company needs to enhance employee motivation and work discipline to achieve better performance. It provides practical contributions for the management of PT. Duta Mitra Lestari in developing strategies to improve employee performance through strengthening motivation and work discipline. Additionally, this research can serve as a reference for future studies focusing on other factors influencing employee performance.